Improved prognosis for acquired aplastic anaemia - Pitcher, L (BMJ Group, 1999)
This study compared the prognosis of patients treated for aplastic anaemia at Great Ormond Street Hospital for Children from 1973-88 (group A; n = 38) with a more recent cohort from 1989-96 (group B; n = 37). The two groups were similar in terms of clinical history, age, and severity of aplasia. The main treatment differences included the use of androgen treatment in group A (21 of 38 patients) but not in group B, and the addition of cyclosporin A to immunosuppressive treatment for 14 patients in group B. Actuarial survival at eight years' follow up was significantly better for group B (84%; 95% CI, 68% to 93%) than for group A (45%; 95% CI, 30% to 60%), because of improved outcome for both immunosuppressive treatment (86% v 39%) and bone marrow transplantation (93% v 56%). There was no evidence for late clonal disorders or secondary malignancies in survivors in either group. The prognosis for aplastic anaemia has improved greatly in recent years so that over 80% of children are long term survivors.